E-Commerce Aksesories Komputer pada Toko UTC Komputer di Medan: Array - Edi, Rahma (Universitas Harapan Medan, 2020)
UTC Computer Medan shop is one of the computer accessories sellers in Medan, UTC computer shop is still lacking in terms of marketing. So it still needs a more massive promotion stage. The proposed online store e-commerce system can handle both online and conventional sales with structured records. To describe the running system, UML (Unified Modeling Language) will be used, which consists of Use Case Diagrams and Activity Diagrams.The UTC Computer Medan shop is one of the sellers of computer accessories in Medan, this UTC computer shop is still lacking in terms of marketing and recording financial reports and sales reports, therefore it is necessary to trade using the internet or using the web as a medium to support business transactions with using E-commerce.The purpose of this research is to design a system and application to be used in the transaction process of selling goods at computer utc stores. The program that will be created is related to entering product data, processing, and displaying information from that data, the system will handle conventional sales transactions while the admin will manage the online store and conventional sales systems simultaneously. Online shop visitors can see products that have been marketed without having to log in, but when visitors want to make purchases of goods, online shop visitors must log in first.From the results of the analysis carried out, there is an ongoing system analysis that has been successfully carried out by interviewing, analyzing and recording user needs, in designing e-commerce online stores that have also been successfully carried out using several design tools and diagrams, and in testing online shops that have been designed successfully implemented.